PENGARUH IMPLEMENTASI GREEN ACCOUNTING, MATERIAL FLOW COST ACCOUNTING, DAN ENVIRONMENTAL PERFORMANCE TERHADAP SUSTAINABLE DEVELOPMENT - Denila Juliani; Lilis Lasmini; Meliana Puspitasari (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
The impact of Environmental Performance, Material Flow Cost Accounting (MFCA), and Green Accounting on Sustainable Development in the healthcare industry listed on the IDX from 2019 to 2023 is examined in this study. To show the relationship between corporate sustainability in the healthcare industry and environmental accounting practices, material use efficiency, and environmental performance, this study will present actual data. Secondary data from annual reports and PROPER ratings are processed in this study using quantitative techniques and Structural Equation Model (SEM) analysis with SmartPLS 4. According to the study findings, Material Flow Cost Accounting significantly affects Sustainable Development, while environmental performance and green accounting have no visible impact. These findings emphasize the importance of operational efficiency in the sustainability of the healthcare sector. This study has limitations in the scope of industry sectors and a limited time period. Therefore, further research is recommended to expand the industry sector or extend the analysis period to understand broader sustainability trends.